LAYANAN BIMBINGAN KELOMPOK UNTUK MENINGKATKAN PEMAHAMAN PEMILIHAN KARIR PESERTA DIDIK KELAS XII IPA 3 SMAN 5 PONTIANAK - Syafitri Syafitri; M. Asrori; Purwanti Purwanti (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractStudents who are already in junior high school and senior high school, it should be have an understanding of his career selection, such as terms and conditions. But what happened in the field was different, there are still some students who have been in grade 12 senior high school who still do not fully understand the career they have chosen. This research was conducted to examine group guidance services to improve understanding of career choices (experiments on students in grade 12 science 3 senior high school 5 Pontianak). The research method used is experiment with pre-experimental research form. The results of research on sub problems one obtained an average of 65,7, and sub problems two obtained an average of 73,14 which means there is an increas from the previous results. The results of research on sub-problems three obtained a value of Sig. (2 tailed) ˂ 0,05, which means that there is a significant difference in the level of understanding of students’ career choices before and after the provision of group guidance services. Based on the results, group guidance services are considered effective for improving understanding of the career choices of grade 12 science 3 senior high school 5 Pontianak.Keyword: Understanding of career selection, Group guidance